An Entropic Approach to Burnout in the Management of a Kitchen Staff Team - Lima, Rui (2022)
Job satisfaction is an important factor in hospitality industry, figuratively, its chimera. A concept has not a single cause; rather, it is the product of elements such as conditions and relationships that determine the workplace, the organizational system of employment, and social, cultural, and economic uncertainties. For example, and as its antonym, Maslach defined burnout “as a psychological syndrome involving motional exhaustion, depersonalization, and a diminished sense of personal accomplishment that occurred among various professionals who work with other people in challenging situations”. This multidimensional approach describes the plight of a three-dimensional concept that is derived empirically, has a similarity with stress, adds an important social dimension to emotional issues such as exhaustion, deper sonalization, and challenging situations, i.e., there is the perception that the entropic state that each kitchen staff team member conveys is relevant for an appropriate personnel management of the kitchen staff team, and mirrors the social dimension that is object of study in this work.